Impacts des produits phytopharmaceutiques sur la biodiversité et les services écosystémiques - Leenhardt, Sophie; Mamy, Laure; Pesce, Stéphane; Sanchez, Wilfried (éditions Quae, 2023)
As part of the Ecophyto II+ plan, INRAE and Ifremer were entrusted in 2020 with the task of conducting a collective scientific assessment on the impacts of plant protection products on biodiversity and ecosystem services. The results, released in May 2022, confirm that all types of terrestrial and aquatic environments, all of their compartments and most of the organisms found there are contaminated by plant protection products. Contamination varies according to the distance from the areas where the products are used, mainly in agriculture. It has direct and indirect impacts on ecosystems, in particular the decline of terrestrial and aquatic invertebrate and bird populations, as well as the alteration of ecosystem functions and services. Different levers contribute to mitigating contamination and its impacts, with varying effectiveness depending on their combination (regulations, conditions of use of products, etc.). This expertise identifies research needs, in particular to better understand dynamic phenomena in a context of multiple pressures on the environment. The aim is to characterise and predict the impacts and to improve the procedures for assessing the risks associated with the use of plant protection products. This book is intended for all actors and decision-makers concerned by the use of plant protection products, whether they are involved in the legal, political, industrial or associative fields, or in research or teaching.